RISK FACTORS FOR LOW BIRTH WEIGHT BABIES AT RSUD KOJA DKI JAKARTA - Meli Deviana; Dina Sulviana Damayanti; Hamidah Hamidah (Universitas Karya Husada Semarang, 2024)
Low birth weight infants (LBW) are one of the causes of high perinatal and neonatal mortality. The prevalence of LBW worldwide reaches 15% of all births, and >97% of them occur in developing countries. The risk of death of premature or LBW infants is 70 times higher than that of full-term infants. The researcher's objective was to determine the risk factors for LBW incidence at Koja Hospital. The research design used was an analytic survey with a retrospective approach, the sampling technique used was purposive sampling with inclusion and exclusion criteria and obtained a sample of 202 people. The results of the study based on the Odds Ratio statistical test showed that mothers with risky parity, risky gestational age, preterm gestational age, anemia, pre-eclampsia and exposure to cigarette smoke had a higher risk of giving birth to LBW babies with odds ratio values; parity 1.75, maternal age 1.003, gestational age 2.909, pre-eclampsia 3.379 and exposure to cigarette smoke 1.690. Based on the results of the research conducted, it is necessary to improve the skills of officers in efforts to detect the risks of pregnant women, fill out the KIA book routinely, provide health information related to healthy pregnancy planning.